2008
DOI: 10.1101/gad.1643308
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin fibrillogenesis regulates three-dimensional neovessel formation

Abstract: During vasculogenesis and angiogenesis, endothelial cell responses to growth factors are modulated by the compositional and mechanical properties of a surrounding three-dimensional (3D) extracellular matrix (ECM) that is dominated by either cross-linked fibrin or type I collagen. While 3D-embedded endothelial cells establish adhesive interactions with surrounding ligands to optimally respond to soluble or matrix-bound agonists, the manner in which a randomly ordered ECM with diverse physico-mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
156
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 74 publications
16
156
0
Order By: Relevance
“…4D). Indeed, it is now well established that sustained activa- tion of MAPK signaling pathway is critical for tubulogenesis, whereas transient activation is insufficient to induce such morphological alterations (8,24,25). Phenotypic quantification of the vascular tubes also confirmed that pretreatment of the HUVECs with PHA665752 (10 −7 M), PD98059 (50 μM) or LY294002 (50 μM) blocked 1K1-NP-induced tubulogenesis (Fig.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…4D). Indeed, it is now well established that sustained activa- tion of MAPK signaling pathway is critical for tubulogenesis, whereas transient activation is insufficient to induce such morphological alterations (8,24,25). Phenotypic quantification of the vascular tubes also confirmed that pretreatment of the HUVECs with PHA665752 (10 −7 M), PD98059 (50 μM) or LY294002 (50 μM) blocked 1K1-NP-induced tubulogenesis (Fig.…”
Section: Resultssupporting
confidence: 50%
“…While free 1K1 and 1K1-NP induced similar levels of ERK phosphorylation at early time points, we observed that the nanoparticle resulted in sustained activation of the MAPK signaling in contrast to free 1K1. In a previous study, the sustained activation of MAPK was reported to be critical for tubulogenesis while a transient activation was shown to be sufficient for the induction of cell proliferation (8,(24)(25). This observation can possibly explain that while 1K1 and 1K1-NP exhibited similar levels of cell proliferation, the latter resulted in enhanced neovascularization in the in vivo matrigel implant and zebrafish angiogenesis assay.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Normal epidermis, which is avascular and does not depend on FN receptors and ligands, is unaffected by changes in MYO1E or FAK function (6,29). On the other hand, complex mesenchymal processes such as neovascularization require the induction of an FN-based ECM (30) and are affected by FAK (31) or MYO1E loss of function (29). Cancer cells produce an FN-rich fibrotic matrix to facilitate metastasis, and both FAK (4, 7) and MYO1E (32) promote carcinogenesis in murine cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…The established, functional upstream domain (FUD) of Streptococcus pyogenes, which efficiently inhibits fibronectin assembly (Tomasini-Johansson et al, 2001;Ensenberger et al, 2004), and its inactive mutant Del29 lacking amino acid residue I 29 (Zhou et al, 2008), were added at 500 nM to HSFs at the time of seeding (7.5 ϫ 10 4 cells/well) into eight-well chamber slides. After incubation for 48 h, the cells were processed and stained with anti-fibrillin-1 and anti-fibronectin antibodies as described in Immunofluorescence Microscopy.…”
Section: Peptide Inhibition and Protein Binding Monitored By Immunoflmentioning
confidence: 99%